Are you coming home mom? Men and woman as household providers and caretakers - Valdivia Santa Cruz, Segundo (2015)
This paper analyses how labor, family and labor-family relationships have changed recently in Peru and analyses also their effects on the household division of work in families where both parents perceive salaries. Our findings focus on: a) the roles of both parents (male and female) as household providers and their views on parenting, b) the scheduling of family activities and labor flexibility, c) the tensions in labor-family relationships d) the social practices related to domestic activities and childcare and e) the struggles for power in daily interactions related to the division of labor.